The Influence Of Service Quality On Consumer Perception Of McDonald’s Gading Serpong - Firlea Zevanka Separgo (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
McDonald's is a widely recognized fast-food chain known for its efficient service and convenience, particularly through its drive-thru options. Despite this, customers have expressed complaints about inconsistencies in food portions and slow service, which can influence their views on service quality. This study aimed to assess how service quality affects consumer perceptions at the McDonald’s Gading Serpong drive-thru. A quantitative approach was taken, using questionnaires distributed to 50 participants, and the data were analyzed through simple linear regression in SPSS. The results indicated that service quality positively and significantly impacts consumer perception, with a correlation (R) value of 0.742 and a significance level of 0.000 (p < 0.05). These results highlight the importance of ensuring consistent food portions to foster positive perceptions among customers at McDonald’s Gading Serpong.